Challenges Related to the Integration of Young Graduates in Morocco - BENNAGHMOUCH , Houssam; MERROUN , Oumaima; BENAMAR , Fatiha (Revue Internationale du Chercheur, 2023)
In this article, we tried to explore the crucial challenge of integrating young graduates into the labor market in Morocco. Recognizing the potential of educated youth as a driving force for socio-economic development, the country seeks their contribution to various professional sectors and innovation. Despite their skills and determination, young Moroccan graduates encounter challenges ranging from intense job market competition to the alignment of academic skills with employer needs. The analysis delves into the skills acquired during university training, emphasizing the role of Moroccan higher education in providing versatile training, developing transversal skills, and promoting practical experience through internships. The Moroccan labor market, pivotal for integration, offers opportunities but also poses challenges such as fierce competition and the necessity to adapt academic skills to market demands. The article underscores the paramount link between academic and professional skills, stressing the need for alignment to ensure successful integration. Challenges faced by young graduates include high unemployment rates, fierce job market competition, and the prevalence of temporary contracts.